What Are the Causes of the Growing Trend of Excess Savings of the Corporate Sector in Developed Countries? An Empirical Analysis of Three Hypotheses - Brufman, Leandro; Martinez, Lisana; Pérez Artica, Rodrigo (World Bank, Washington, DC, 2013)
This paper analyzes annual accounting data for a sample of 5,000 publicly traded manufacturing firms from Germany, France, Italy, Japan, and the United Kingdom. The analysis uses data from 1997 to 2011 and finds an increasing trend of excess savings (defined as the difference between gross saving and capital formation) and a gradual decline of gross capital formation. This trend is accompanied by a steady deleveraging process and a decrease in the share of operating assets in total assets. This process is more acute among the more credit constrained, the more volatile, and the less dynamic firms.